PECULIARITIES OF SPECIALISTS’ PROFESSIONAL DEVELOPMENT NOWADAYS: THEORETICAL ASPECTS - Babushko, Svitlana R. (Educological discourse, 2014)
The article represents the analysis of transformation changes taking place nowadays in employees’ training, one of the constituents of professional development. It has been shown that “technical skills” training of employees in the past is currently and effectively being combined with “soft skills” training. Their content has been revealed and there have also been defined their two distinguishing features which are characteristic of modern employees’ training: innovation and informalization. Innovation implies not only the employees’ ability to work with innovative technologies, but rather the development of employees’ ability to acquire new knowledge on their own. Informalization of employees’ training is displayed through getting new knowledge and skills due to their experience and communication.